2013
DOI: 10.1111/bph.12344
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis inhibitors in cancer therapy: mechanistic perspective on classification and treatment rationales

Abstract: Angiogenesis, a process of new blood vessel formation, is a prerequisite for tumour growth to supply the proliferating tumour with oxygen and nutrients. The angiogenic process may contribute to tumour progression, invasion and metastasis, and is generally accepted as an indicator of tumour prognosis. Therefore, targeting tumour angiogenesis has become of high clinical relevance. The current review aimed to highlight mechanistic details of anti-angiogenic therapies and how they relate to classification and trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
179
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(191 citation statements)
references
References 231 publications
2
179
0
4
Order By: Relevance
“…We were able to observe a positive correlation between the R 1 values of lipids and absolute pO 2 When all the data were pooled, a significant correlation was established between the R 1 values of lipids and the pO 2 values (P ¼ 0.0275, r ¼ 0.3726; Fig. 4).…”
Section: Mobile Enables the Follow-up Of Positive And Negative Variatmentioning
confidence: 68%
See 1 more Smart Citation
“…We were able to observe a positive correlation between the R 1 values of lipids and absolute pO 2 When all the data were pooled, a significant correlation was established between the R 1 values of lipids and the pO 2 values (P ¼ 0.0275, r ¼ 0.3726; Fig. 4).…”
Section: Mobile Enables the Follow-up Of Positive And Negative Variatmentioning
confidence: 68%
“…A change in the R 1 of lipids is related to a change in the tumor pO 2 While pooling data from 20 different tumors (10 of each tumor model), we can observe a significant correlation between the DR 1 of lipids (MOBILE) and the DpO 2 in the same tumors (P ¼ 0.0059, r ¼ 0.5097; Fig. 2A), whereas similar analysis using the global R 1 does not give a significant correlation (Fig.…”
Section: Mobile Enables the Follow-up Of Positive And Negative Variatmentioning
confidence: 85%
“…In addition, a separate study showed that 9 out of 11 animals maintained on the UKD and treated with radiation had complete and sustained remission of their implanted tumors, even after being switched back to a standard rodent diet ( 58 ). Another recent study Tumors not only stimulate rapid angiogenesis, but these blood vessels often develop immaturely and become very leaky ( 52 ). This can lead to an increased infl ux of infl ammatory cells and signaling that can actually perpetuate tumor growth and damage surrounding normal tissue.…”
Section: Kd As An Adjuvant Therapymentioning
confidence: 99%
“…One of the challenges researchers initially faced was the selection of scientifically and technically efficient methods for assessing the endothelial response to candidate angiogenesis inhibitors [5]. Ideally, an assay should be valid, methodologically straightforward, easily quantifiable, cost-effective and able to provide an environment simulating the natural angiogenic process under study.…”
Section: Introductionmentioning
confidence: 99%